2017
DOI: 10.4103/1008-682x.183379
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin ameliorates the adverse effects of leptin on sperm

Abstract: This study examined the effects of melatonin on leptin-induced changes in sperm parameters in adult rats. Five groups of Sprague-Dawley rats were treated with either leptin or leptin and melatonin or melatonin for 6 weeks. Leptin was given daily via the intraperitoneal route (60 μg kg−1 body weight) and melatonin was given in drinking water (10 mg kg−1 or 20 mg kg−1 body weight per day). Upon completion, sperm count, sperm morphology, 8-hydroxy-2-deoxyguanosine, Comet assay, TUNEL assay, gene expression profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“… 30 31 Even though ROS is needed at low concentration for sperm capacitation and acrosomal reaction, at high concentrations, it is capable of causing damage in a cascade of reactions involving a wide range of biomolecules. 27 32 33 34 Male reproductive organs and gametes are particularly vulnerable to oxidative damage, as testicular tissue and sperm plasma membranes are rich in polyunsaturated fatty acids (PUFA). 35 36 When targeting lipids, oxidant compounds can induce a peroxidation chain reaction that produces several toxic lipid aldehyde species including MDA and 4-HNE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 31 Even though ROS is needed at low concentration for sperm capacitation and acrosomal reaction, at high concentrations, it is capable of causing damage in a cascade of reactions involving a wide range of biomolecules. 27 32 33 34 Male reproductive organs and gametes are particularly vulnerable to oxidative damage, as testicular tissue and sperm plasma membranes are rich in polyunsaturated fatty acids (PUFA). 35 36 When targeting lipids, oxidant compounds can induce a peroxidation chain reaction that produces several toxic lipid aldehyde species including MDA and 4-HNE.…”
Section: Discussionmentioning
confidence: 99%
“…Smears were stained with Eosin Y (Leica Biosystems Richmond Inc., Buffalo Grove, IL, USA) and spermatozoa with the following morphologies were considered to be abnormal: (i) headless, (ii) hookless, (iii) double headed, (iv) broken tail, (v) coiled tail, and (vi) double tailed. 27 28 …”
Section: Methodsmentioning
confidence: 99%
“…Whilst all its effects are not yet confirmed, there are clear implications for regulating food intake, body weight, the hypothalamic–pituitary–thyroid and hypothalamic–pituitary–growth hormone axes, bone formation and inflammation 81 . Rodent models also show that exogenous leptin has direct toxic effects on developing spermatocytes, resulting in reduced sperm count, reduced normal morphology and increased ROS and DNA damage 82–84 . Whilst similar studies have not been performed in humans, leptin receptors are present on germ cells and Leydig cells of human testis, and expression is increased in infertile populations, suggesting a similar mechanism 85,86 …”
Section: Why There May Be Descrepancies As To the Effect Of Obesity O...mentioning
confidence: 99%
“…A more recent study using 60 μg kg −1 body weight of leptin also reached the same conclusions 67. Researchers in the latter studies also found evidence of increased reactive oxygen species (ROS)66 levels, high 8-hydroxy-2-deoxyguanosine (8-OHdG) levels, and increased sperm DNA fragmentation6768 after administering leptin. Incidentally, leptin has been shown to induce ROS formation in phagocytic6970 and nonphagocytic7172 cells and in renal tubular cells by activating nicotinamide adenine dinucleotide phosphate (reduced form) (NADPH) oxidase 73.…”
Section: Leptin and Male Infertilitymentioning
confidence: 61%
“…Thus, leptin may increase sperm damage by generating ROS in the seminiferous tubular cells or in the epididymis. That oxidative stress might indeed be involved is also supported by findings that these adverse effects of leptin are prevented by concurrent administration of melatonin, a very powerful antioxidant 68…”
Section: Leptin and Male Infertilitymentioning
confidence: 75%